Inhibition of microbial pathogens by riboflavin, ultraviolet A and selected antibiotic combinations / Aarthi Ahgilan - Aarthi, Ahgilan (2017)
Blood infection remains as a major global public health problem. The World Health Organisation (WHO) estimates that 8 million new cases and 3 million deaths are directly attributed to the disease each year. The most common blood infections may lead to septicaemia if left untreated. In recent decades, pathogens have become resistant towards conventionally available antibiotics. This phenomenon persistently proliferates while increasing the number of individuals suffering from diseases and morbidity. In consequence, a pressing need arises for more effective antimicrobial agent to inhibit these infectious pathogens. One specific biomaterial of interest known as riboflavin or vitamin B2 has been shown to exhibit antimicrobial properties when activated with ultraviolet A (UVA) irradiation. Randomly selected blood borne pathogens Staphylococcus aureus, Enterococcus faecalis, Salmonella typhi, Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae and Candida albicans were tested by using disc diffusion method. The antimicrobial properties of riboflavin by UVA at 365 nm, with or without irradiation were tested. They were tested with (negative control), disc with stand-alone UVA irradiated riboflavin (50.0 μl), and disc with stand-alone riboflavin combined with pre-treated standard drugs for 5 minutes. The zones of inhibition were measured in millimetres. Collected data expressed as (mean ± standard deviation) and one way ANOVA and Post- Hoc Tukey’s multiple comparison tests (p value was p<0.05) were done. The findings showed that stand-alone riboflavin without UVA exposure inhibited S. aureus, E. faecalis, S. typhi, and P. aeruginosa at a range of 20.0 ± 1.0, 17.7 ± 0.6, 17.3 ± 0.6, and 15.7 ± 0.6 respectively. Intermediate zones of inhibition were observed for E. coli and C. albicans in the range of 11.7 ± 0.6 and 11.7 ± 0.6 respectively. K. pneumoniae was the only pathogen that was resistant with a range of 7.7 ± 0.6 mm using the 50.0 μl of riboflavin solution. The mean difference of stand-alone riboflavin was also found to be significant against activated riboflavin with UVA at 365 nm at p = 0.001 level (p<0.05). Moreover, selected pathogens such as S. aureus, E. faecalis, S. typhi, and P. aeruginosa showed zones of inhibition significant at p = 0.001 after pre-treatment with standard drugs and then with riboflavin compared to standard drugs alone. The antimicrobial efficacy of riboflavin without the need for irradiation using UVA exposure for the microbial isolates tested was shown for the first time in this study. Furthermore, previous treatments with standard drugs and then with riboflavin application significantly inhibited the growth of the selected pathogens. This combinational or stand-alone riboflavin application could be further explored for enhanced management of blood borne pathogens.